Online Family Problem Solving for Pediatric Traumatic Brain Injury: Influences of Parental Marital Status and Participation on Adolescent Outcomes. Issue 3 (May 2018) - Raj, Stacey P.; Zhang, Nanhua; Kirkwood, Michael W.; Taylor, H. Gerry; Stancin, Terry; Brown, Tanya M.; Wade, Shari L.
Abstract : Objective: To examine the moderating effects of parent marital status and participation on efficacy of an online family problem-solving intervention for pediatric traumatic brain injury (TBI). Methods: Participants were 132 adolescents (12-17 years) who had sustained a recent (<6 months) TBI and their parents. Participants were randomly assigned to the intervention (Counselor-Assisted Problem Solving, CAPS) or an Internet resource comparison (IRC) condition. CAPS was designed to support families in the initial phase following TBI, by teaching problem-solving skills and addressing common challenges. To examine the moderating effect of parent marital status, participants were divided into 4 groups (ie, CAPS married household, CAPS unmarried household, IRC married household, and IRC unmarried household). Family income and caregiver education were controlled in analyses. Results: Parent marital status moderated treatment effects on adolescent externalizing behavior problems. Adolescents from married households in CAPS displayed fewer behavior problems at 6 and 18 months postbaseline compared with adolescents from unmarried households in CAPS. Among married CAPS families, there were no differences in outcomes among families where 1 or 2 parents actively participated. Conclusions: Web-based interventions for pediatric TBI, such as CAPS, are a viable option for some although not all families. Further research is needed to investigate factors that influence efficacy to match families to the most beneficial treatments.